MANAJEMEN DAKWAH KH. SHOLEH BAHRUDIN DALAM PEMBINAAN KARAKTER SOSIAL SANTRI - Umi Nadziro; Miftahur Rokhmah; Ahmad Irsyad; Anang Sholikhudin (Al-Insyirah: Jurnal Pendidikan dan Konseling Islam, 2026)
This study aims to analyze the concept of da'wah management from the perspective of KH. Sholeh Bahrudin and its contribution to shaping the social character of santri. The study is motivated by the growing importance of Islamic education in fostering social values, particularly in response to the challenges of modernization, which often weaken students’ sense of empathy, cooperation, and tolerance. Although numerous studies have examined da'wah management and character education separately, limited research has explored KH. Sholeh Bahrudin’s da'wah management framework and its relevance to the development of santri’s social character. This gap forms the basis of the present study. The research employs a qualitative descriptive approach using library research and content analysis of KH. Sholeh Bahrudin’s thoughts and related literature. The findings reveal that his concept of da'wah management consists of three main stages: planning, implementation, and evaluation, all of which emphasize a humanistic, contextual, and value-oriented approach. The implementation of these principles contributes significantly to the development of santri’s social character, including caring, mutual cooperation, and tolerance. Therefore, effective da'wah management can serve as a strategic approach to cultivating a generation that is not only grounded in Islamic values but also possesses strong social awareness